ASSESSING THE DRIVERS, BARRIERS AND ENVIRONMENTAL FACTORS IN THE ADOPTION OF SOLAR ENERGY: EMPIRICAL EVIDENCE FROM PAKISTAN - Aqil Khan; Naveed Ali; Samia Manan; Lala Rukh (International Journal of Contemporary Issues in Social Sciences, 2023)
The role of solar energy adoption as a viable solution to combat climate change, aligned with the objectives of the United Nations Sustainable Development Goals (SDGs). Many countries have extensively achieved goals of their renewable energy policies. For the same purpose, Pakistan has also imposed various renewable energy policies to convert their fossils fuel energy into renewable energy. However they always fail to achieve its targeted objectives. This study investigates that how socio-economic and environmental factors are responsible for the non-impressive share of renewable energy into the energy max. Based on the survey of 373 respondents from district Peshawar, logistic regression model was employed to investigate the impact of various factors on the solar adoption. In results it is concluded that socio-economic factors including: increase in property value, neighbor’s participation and easily availability of solar system in the market has positive and statistically significant impacts solar adoption behavior. Although, high initial cost of solar system, unawareness of community regarding benefits of solar energy, fear of theft and non-availability of installment plans remain barriers in the ways of solar adoption. Moreover it has also been found that the culture of research and development for innovations in solar technology, and environmental sustainability due to solar system can be factors of motivation for the potential consumers to diffuse solar technology. As per results, it is recommended that government should start awareness campaign regarding benefits of solar energy. Moreover, solar related should be declared as tax free product to encourage local production at minimal costs.